Governing traditional medicine in Kenya: Problematization and the role of the constitution. Issue 2 (3rd April 2018) - Harrington, John
ABSTRACT: After decades of repression and neglect, traditional medicine in Kenya has become the object of increasing official attention in recent years. Initiatives have been proposed by a range of state bodies and civil society groups to regulate practice and to protect the traditional knowledge on which it is based. These are informed by the work of international bodies with which agencies and groups are closely connected. This article draws on governmentality theory in mapping these developments accounting specifically for international and national influences on the current wave of reform. It argues that initiatives are cast in normative, epistemic and rhetorical terms as responses to problems faced by the Kenyan state. Governance technologies deployed or proposed are oriented to the 'problematization' of traditional medicine in terms of health and safety, threats to sovereignty and national development. The Constitution of Kenya 2010 (CoK) provides a crucial normative anchor for each of these problematizations. Its specific provisions allow international imperatives to be re-articulated in terms of the national interest.